A new cycloartane triterpenoid glycoside from Souliea vaginata. Issue 21 (2nd November 2017) - Wu, Hai-Feng; Liu, Xin; Zhu, Yin-Di; Zhou, Jing; Gong, Ying-Ying; Ma, Guo-Xu; Xu, Xu-Dong; Liu, Yi-Lin; Luo, Zheng-Hong; Chen, Di-Zhao; Zou, Qiong-Yu; Zhao, Zi-Jian
Abstract: One new cycloartane triterpenoid glycoside, soulieoside Q (1 ), together with four known compounds (2 −5 ) were isolated from the ethanolic extract of the rhizomes of Souliea vaginata Maxim. The structure of the new compound was determined by extensive spectroscopic analysis including 1D and 2D NMR and HRESIMS, as well as chemical methods. Compound1 was evaluated for its cytotoxic activities against HepG2 and A549 cancer cell lines. Graphical Abstract: